2023
DOI: 10.3389/feduc.2023.1333415
|View full text |Cite
|
Sign up to set email alerts
|

Below average ChatGPT performance in medical microbiology exam compared to university students

Malik Sallam,
Khaled Al-Salahat

Abstract: BackgroundThe transformative potential of artificial intelligence (AI) in higher education is evident, with conversational models like ChatGPT poised to reshape teaching and assessment methods. The rapid evolution of AI models requires a continuous evaluation. AI-based models can offer personalized learning experiences but raises accuracy concerns. MCQs are widely used for competency assessment. The aim of this study was to evaluate ChatGPT performance in medical microbiology MCQs compared to the students’ per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
7
2
Order By: Relevance
“…Herrmann-Werner et al demonstrated a lower level of ChatGPT performance in the lower cognitive skills in contrast to the findings of this study [44]. To the contrary, a recent study that assessed ChatGPT-3 performance in medical microbiology MCQs showed a trend similar to our findings where the AI model performed at a higher level in the lower cognitive domains [45]. This divergence of findings suggests the need for more comprehensive studies to discern the abilities of AI models in different cognitive domains, which would be helpful to guide improvements in these models and to enhance their utility in higher education.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Herrmann-Werner et al demonstrated a lower level of ChatGPT performance in the lower cognitive skills in contrast to the findings of this study [44]. To the contrary, a recent study that assessed ChatGPT-3 performance in medical microbiology MCQs showed a trend similar to our findings where the AI model performed at a higher level in the lower cognitive domains [45]. This divergence of findings suggests the need for more comprehensive studies to discern the abilities of AI models in different cognitive domains, which would be helpful to guide improvements in these models and to enhance their utility in higher education.…”
Section: Discussioncontrasting
confidence: 61%
“…Notably, cognitive errors were more prevalent in “Remember” and “Understand” categories. Another recent study demonstrated that ChatGPT-3.5 correctly answered 64 of 80 medical microbiology MCQs, albeit below student averages, with better performance in the “Remember” and “Understand” categories and more frequent errors in MCQ with longer choices in terms of word count [45].…”
Section: Introductionmentioning
confidence: 99%
“…Herrmann-Werner et al demonstrated a lower level of ChatGPT performance in the lower cognitive skills in contrast to the ndings of this study [44]. To the contrary, a recent study that assessed ChatGPT-3 performance in medical microbiology MCQs showed a trend similar to our ndings where the AI model performed at a higher level in the lower cognitive domains [45]. This divergence of ndings suggests the need for more comprehensive studies to discern the abilities of AI models in different cognitive domains, which would be helpful to guide improvements in these models and to enhance their utility in higher education.…”
Section: Discussioncontrasting
confidence: 54%
“…Meyer et al emphasized the importance of students' engagement as prompt creators and fact checkers in an educational framework, rather than simply relying on AI-produced material 63 . Multiple recent studies highlighted the need to revise the current assessment methods in higher education in light of the high performance of LLMs in various exams [66][67][68][69] . www.nature.com/scientificreports/ Based on the prospects of ChatGPT in higher education, a previous study explored the validity of a survey instrument to assess the factors influencing the adoption of this novel tool among university students in health schools in Jordan 51 .…”
Section: Discussionmentioning
confidence: 99%